2006
DOI: 10.1051/parasite/2006133193
|View full text |Cite
|
Sign up to set email alerts
|

New filarial nematode from Japanese serows (Naemorhedus crispus: Bovidae) close to parasites from elephants

Abstract: Summary :A new onchocercid species, Loxodontofilaria caprini n. sp. (Filarioidea: Nematoda), found in subcutaneous tissues of 37 (33 %) of 112 serows (Naemorhedus crispus) examined in Japan, is described. The female worm had the characteristics of Loxodontofilaria, e.g., the large body size, well-developed esophagus with a shallow buccal cavity, and the long tail with three caudal lappets. The male worm of the new species, which was first described in the genus, had unequal length of spicules, 10 pairs of pre-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 11 publications
1
15
0
Order By: Relevance
“…Filarioids from elephants, Loxodontofilaria Berghe & Gillain, 1939, were not well known and provisionally placed in the Dipetalonema line (Bain, Baker, Chabaud, 1982, in Chabaud & Bain, 1994. With the recent discovery of a species of Loxodontofilaria in a caprine (Uni et al, 2006), a molecular analysis was performed which lead to a different interpretation. It indicates close relationships with Onchocerca Diesing, 1841 (work in progress), although the vagina of Loxodontofilaria has distinct bend and chamber, contrary to Onchocerca.…”
Section: Is the Dipetalomema Lineage A Reality?mentioning
confidence: 99%
“…Filarioids from elephants, Loxodontofilaria Berghe & Gillain, 1939, were not well known and provisionally placed in the Dipetalonema line (Bain, Baker, Chabaud, 1982, in Chabaud & Bain, 1994. With the recent discovery of a species of Loxodontofilaria in a caprine (Uni et al, 2006), a molecular analysis was performed which lead to a different interpretation. It indicates close relationships with Onchocerca Diesing, 1841 (work in progress), although the vagina of Loxodontofilaria has distinct bend and chamber, contrary to Onchocerca.…”
Section: Is the Dipetalomema Lineage A Reality?mentioning
confidence: 99%
“…In addition, Onchocerca-like microfilariae larger than those of O. dewittei japonica were observed in 44 % of wild boar during this study and provisionally referred to Onchocerca sp. Adult worms found in a Japanese serow, in Oita, identified to O. suzukii Yagi, Bain & Shoho, 1994(cited in Takaoka et al, 2004, were reidentified to Loxodontofilaria caprini Uni & Bain, 2006(Uni et al, 2006. The vectors of these four species are not known, except for O. skrjabini, which is transmitted by two Simulium species in Europe (Schulz-Key & Wenk, 1981).…”
Section: Introductionmentioning
confidence: 99%
“…To investigate the transmission and the background of this zoonotic onchocerciasis, we have examined filariae from wild ungulates in Japan, the wild boar Sus scrofa Linnaeus, 1758, the sika deer Cervus nippon Temminck, 1838, the serow Naemorhedus crispus (Temminck, 1845), as well as cattle (Bos taurus), and the putative vectors, the black flies (Diptera: Simuliidae). These studies showed a great diversity among the genus Onchocerca as well as other Onchocercinae (Takaoka et al, 1989;Takaoka, 1990Takaoka, , 1994Takaoka & Bain, 1990;Yagi et al, 1994;Uni et al, 2001Uni et al, , 2002Uni et al, , 2004Uni et al, , 2006Uni et al, , 2007. The picture of the filarial fauna is however still incomplete, and a few kinds of microfilariae, without corresponding adult worms, remain unidentified.…”
mentioning
confidence: 99%
“…Type A is presumed to be identical to type I from black flies collected in a cattle shed (Takaoka & Bain, 1990). It had been suggested that type I was L. caprini, adult worms of which were found in a serow Naemorhedus crispus (= Capricornis crispus) (Temminck, 1845) in Oita (Uni et al, 2006). However, in our previous study (Fukuda et al, 2008) sity of this genus in Japanese wild ruminants is still not completely understood.…”
Section: Discussionmentioning
confidence: 93%